Urinary Polycyclic Aromatic Hydrocarbons in a Longitudinal Cohort of Children with CKD: A Case of Reverse Causation?. Issue 6 (30th June 2022) - Jacobson, Melanie H.; Wu, Yinxiang; Liu, Mengling; Kannan, Kurunthachalam; Lee, Sunmi; Ma, Jing; Warady, Bradley A.; Furth, Susan; Trachtman, Howard; Trasande, Leonardo
Key Points: Serially measured polycyclic aromatic hydrocarbon (PAH) metabolites were associated with increased eGFR and lower proteinuria. PAHs were associated with higher tubular injury and oxidant stress biomarkers. Reduced renal function may affect excretion of urinary PAHs. Visual Abstract: Abstract : Background: Air pollution, which results in the formation of polycyclic aromatic hydrocarbons (PAHs), has been identified as a cause of renal function decline and a contributor to CKD. However, the results of cross-sectional studies investigating personal, integrated biomarkers of PAHs have been mixed. Longitudinal studies may be better suited to evaluate environmental drivers of kidney decline. The purpose of this study was to examine associations of serially measured urinary PAH metabolites with clinical and subclinical measures of kidney function over time among children with CKD. Methods: This study was conducted among 618 participants in the Chronic Kidney Disease in Children study, a cohort study of pediatric patients with CKD from the United States and Canada, between 2005 and 2015. In serially collected urine samples over time, nine PAH metabolites were measured. Clinical outcomes measured annually included eGFR, proteinuria, and BP. Subclinical biomarkers of tubular injury (kidney injury molecule-1 [KIM-1] and neutrophil gelatinase-associated lipocalin [NGAL]) and oxidant stress (8-hydroxy-2′-deoxyguanosine [8-OHdG] and F2 -isoprostane) were assayed in urine samples. Results: Children were followed over an average (SD) of 3.0 (1.6) years and 2469 study visits (mean±SD, 4.0±1.6). Hydroxynaphthalene (NAP) or hydroxyphenanthrene (PHEN) metabolites were detected in >99% of samples and NAP concentrations were greater than PHEN concentrations. PHEN metabolites, driven by 3-PHEN, were associated with increased eGFR and reduced proteinuria, diastolic BP z-score, and NGAL concentrations over time. However, PAH metabolites were consistently associated with increased KIM-1 and 8-OHdG concentrations. Conclusions: Among children with CKD, these findings provoke the potential explanation of reverse causation, where renal function affects measured biomarker concentrations, even in the setting of a longitudinal study. Additional work is needed to determine if elevated KIM-1 and 8-OHdG excretion reflects site-specific injury to the proximal tubule mediated by low-grade oxidant stress.